PENERAPAN METODE PROBLEM SOLVING UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM DI SDN 07 INDRALAYA UTARA - Junaidah, Junaidah (Jurnal Ilmiah Bina Edukasi, 2020)
This study aims to determine the improvement of student learning outcomes in Pendidikan Agama Islam subjects by applying the Problem Solving method. The research was conducted in Semester Ganjil 2019. This research was a Classroom Action Research (CAR which consisted of two cycles. Subjects in this study were sixth grade students of SD Negeri 07 Indralaya Utara, totaling 21 students. Data collection techniques used were observation and The results showed that in the first cycle, 66.67% of students obtained mastery learning in KKM 70. In Cycle II, mastery learning increased to 90.4% of students who achieved KKM 70. So, it can be concluded that learning using the Problem method Solving can improve student learning outcomes in Pendidikan Agama Islam subjects